Prospects for Illinois steam coal in the Pacific export market : an overview - T. J. Kim; S. Suh (Society for Mining, Metallurgy & Exploration, 1988)
The purpose of this paper is to evaluate overall prospects of the export market in the Pacific Rim for Illinois steam coal in terms of recent changes in global socioeconomic factors. To pursue this objective, three factors affecting the prospects of Illinois coal in the Asian market were selected for detailed analysis: quality requirements of imported coal, particularly those of the Japanese market; import controls and regulatory factors; and transportation factors affecting the export of Illinois coal. Based on these analyses, alternative long-term strategies are suggested for promoting Illinois coal export in the Asian market.